Research on the impact of urban-rural integration on rural land use efficiency in China - Liu, Hongxin; Liu, Xiaoxin (Frontiers in Environmental Science, 2025)
As a core strategy in China’s modernization process during the new era, urban-rural integration development is imperative for expanding the development space of Chinese-style modernization and advancing high-quality growth. This paper uses the panel data of provincial levels in China from 2012 to 2023 to construct a three-level indicator system to measure the level of urban-rural integration and rural land utilization efficiency in China’s provinces, and explores the impact mechanism of China’s urban-rural integration on rural land utilization efficiency. Findings include: (1) Urban-rural integration significantly enhances rural land use efficiency; (2) Mechanism analysis demonstrates that urban-rural integration boosts land transfer rates and labor mobility between urban and rural areas, thereby improving land use efficiency; (3) Regional heterogeneity analysis reveals stronger promoting effects in eastern and western regions, with statistically insignificant impacts in central China. Policy recommendations are proposed, focusing on establishing market-driven resource allocation mechanisms, implementing region-specific policies, and improving collaborative governance of land transfer and labor mobility. This research provides empirical support for deepening the theory of urban-rural integration, optimizing the allocation of land resources, formulating differentiated policies, and resolving regional development imbalances.